C Primer Plus, Fifth Edition - Prata, Stephen (Sams, 2004)
The new classic! C Primer Plus, now in its 5th edition, has been revised to include over 20 new programming exercises, newly improved examples and the new ANSI/ISO standard, C99. Task-oriented examples will teach you the fundamentals of C programming. From extended integer types and compound literals to Boolean support and variable-length arrays, you will learn to create practical and real-world applications with C programming. Review questions and programming exercises at the end of each chapter will reinforce what you have learned. This friendly and easy-to-use self-study guide will help you understand the fundamentals of this core programming language.
Keywords: C (Computer program language); C (Langage de programmation)